MEDIA SOSIAL DAN IDENTITAS BUDAYA : KAJIAN ANTROPOLOGI POSTMODERNISME - Sulfianti Panggalinan; Aswar; Shaskia Hani Putri; Sri Malem Br Bangun (STKIP Subang, 2026)
The rapid development of social media has transformed the way people form and organize cultural identities in the postmodern era. In this context, issues of identity fragmentation, fluid cultural claims, and the dominance of popular culture that blur the lines between the local and the global have emerged, raising questions about how to understand cultural identity within the logic of symbolic capitalism and visual consumption. The purpose of this article is to analyze the role of social media in the formation of cultural identity from a postmodern anthropological perspective, by examining the dynamics of symbolic hegemony, cultural consumption, and users' digital practices. This research employs a descriptive qualitative approach with content analysis and literature review of postmodernist theories (Baudrillard, Lyotard, and Foucault), as well as empirical data drawn from observations of social media posts and in-depth interviews with active users. The results reveal that cultural identity is not fixed and singular, but rather dynamic, personalized, and a performative construction visible through practices such as the choice of emojis, filters, hashtags, and recommendation algorithms. Social media becomes a space for negotiating cultural meanings, which also reinforces the fragmentation, simulation, and commodification of identity. These findings emphasize the importance of a digital anthropological approach in understanding the complexity of cultural identity amidst the hegemony of symbolic capitalism and the fragmentation of reality on social media.